Pelatihan Aplikasi LaTeX Bagi Guru-guru SMP Negeri 1 Insana, Kabupaten Timor Tengah Utara - Luan, Faustianus; Sikas, Oktovianus R.; Kelen, Yoseph P.K.; Liunokas, Ebenhaiser; Bano, Elinora N. (Dedikasi Sains dan Teknologi (DST), 2023)
The aim of the community partnership program is to improve the thinking skills or increase the skills of PKM participating teachers in mastering LaTeX applications. This service aims to introduce LaTeX applications for teachers of SMP Negeri 1 Insana, North Central Timor Regency (TTU Regency) to create documents other than using Ms.Word. LaTeX software is a word processor that has advantages in the availability of symbols and environmental settings for mathematical formulas and others. Therefore, LaTeX is starting to be frequently used by educators, more specifically in the field of mathematics, in preparing lesson materials, be it textbooks, articles, RPS, student worksheets (LKPD), or other documents. This service activity is carried out in the form of mentoring or training using demonstration, practice, and discussion methods, which is carried out offline in the presence of four accompanying lectures and six students. The results of the activity show that the participants (in this case, the teachers) can run LaTeX programs and can create simple teaching material templates that contain mathematical symbols and formulas quite well. Participants also believed that LaTeX was very necessary in preparing documents for learning in various fields, especially for educators today.